Restraint Stress Impairs Glucose Homeostasis Through Altered Insulin Signalling in Sprague-Dawley Rat (Nigerian Journal of Physiological Sciences, 2021)
Summary: The study investigated the potential alteration in the level of insulin and adiponectin, as well as the expression of insulin receptors (INSR) and glucose transporter 4 GLUT-4 in chronic restraint stress rats. Sprague-Dawley rats were randomly divided into two groups: the control group and stress group in which the rats were exposed to one of the four different restraint stressors; 1 h, twice daily for a period of 7 days (S7D), 14 days (S14D) and 28 days (S28D). Glucose tolerance and insulin sensitivity were evaluated following the final stress exposure. ELISA were performed to assess the level of insulin and adiponectin as well as expression of INSR and GLUT4 protein in skeletal muscle. Plasma corticosterone level was also determined as a marker of stress exposure. Restraint stress for 7 days caused transient glucose intolerance, while S14D rats demonstrated increased glucose intolerance and insulin insensitivity. However, restraint stress for 28 days had no effect on glucose tolerance, but did cause an increase in glucose response to insulin challenge. The serum level of adiponectin was significantly (p< 0.05) lower compared with the control value while insulin remained unchanged except at in S28D rats that had a significant (p